2015
DOI: 10.1007/s00339-015-9180-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of chemical ordering and fragility for Ge–Se–In glasses

Abstract: Decreasing the band gap of a material due to metal impurities has been approved through several studies, and this subject is considered as a major area of interest within the optoelectronic applications. Indium-based chalcogenides have been considered good candidates in nonlinear optics due to their ability to transmit in the infrared region. Hence, Ge 18 Se 82 has been alloyed with In. The nature of the chemical ordering of amorphous samples of Ge 18 Se 82-x In x (x = 0, 2, 4 and 6) have been systematically s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…As noticed from results, the (m opt ) and (r opt ) decreased when film thickness increased. That performance is accorded with other previous researches [47].…”
Section: R E T R a C T E Dsupporting
confidence: 92%
See 1 more Smart Citation
“…As noticed from results, the (m opt ) and (r opt ) decreased when film thickness increased. That performance is accorded with other previous researches [47].…”
Section: R E T R a C T E Dsupporting
confidence: 92%
“…The dielectric constants (e 1 ), the real part, (e 2 ) the imaginary part of CCTS 4 thin films were evaluated from the extinction coefficient (k) and refractive index (n) magnitudes through the equations [47,48]:…”
Section: Optoelectronic Characterization 241 Dielectric Constantsmentioning
confidence: 99%
“…The assessed values of E g th are depicted in Table 3 and are observed to decrease as Sn-content is increased. These results are supported by the decrease in average single bond energy defined by the ratio of < H s > to< r > [26]. The values of average single bond energy are also found to decrease with the incorporation of Sn.…”
Section: Theoretical Bandgap and Average Heat Of Atomizationmentioning
confidence: 58%
“…From the tabulated values, it is found that T g increases with an increase in rigidity of the system, degree of cross linking and average bond strength. Hence, we interpret that the observed variation of glass transition temperature with Bi content is due to the dependence of T g on the connectivity [33]. Inset in Fig.…”
Section: Correlation Between Mean Bond Energy E and Glass Transition mentioning
confidence: 59%